2023
DOI: 10.1186/s12889-023-15042-x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of sleep duration with incident cardiovascular outcomes: a prospective study of 33,883 adults in a general population

Abstract: Background Studies on the effect of sleep duration on cardiovascular health have contradictory findings. Underlying health issues may have led to inconsistent results and warrant consideration. We aim to assess the relationship of night sleep duration with incident cardiovascular disease (CVD) in a general population, taking into consideration underlying chronic diseases. Methods Data from Shanghai Suburban Adult Cohort and Biobank with a median fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…We report novel discovery of 22 gene-sleep duration interaction loci for BP traits -12 for short sleep, and 10 for long sleep. Several of the identified variants are rare with allele frequency <=1%, with four variants identified in sex-stratified metaanalyses, and 18 variants specific to either the AFR(1), EUR (6), or HIS (11) population groups. In line with our previous research, the identified genomic loci exhibiting interactions with short and long sleep are non-overlapping (with non-significance in the opposing sleep duration exposure), suggesting distinct mechanisms influencing cardiovascular health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We report novel discovery of 22 gene-sleep duration interaction loci for BP traits -12 for short sleep, and 10 for long sleep. Several of the identified variants are rare with allele frequency <=1%, with four variants identified in sex-stratified metaanalyses, and 18 variants specific to either the AFR(1), EUR (6), or HIS (11) population groups. In line with our previous research, the identified genomic loci exhibiting interactions with short and long sleep are non-overlapping (with non-significance in the opposing sleep duration exposure), suggesting distinct mechanisms influencing cardiovascular health.…”
Section: Discussionmentioning
confidence: 99%
“…The role of long sleep is more elusive, with recent work highlighting the pertinence of inflammatory markers, underlying comorbidity burden (i.e. dyslipidemia, depression) and arterial stiffness metrics 5,6 . This incomplete understanding of the intersection between habitual sleep duration and cardiovascular health necessitates further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…99 Poor sleep quality and quantity are both known to increase the risk of incident CVD. [100][101][102][103] Therefore, special attention should be paid to noise reduction during sleep. Personal measures to reduce the effect of noise during sleep have mainly been studied in the hospital setting.…”
Section: The Importance Of Sleep-nighttime Noise Is Strongly Associat...mentioning
confidence: 99%
“…The most dated studies do not support this correlation [ 226 ]. However, recent evidence suggest a link between sleep duration and CVD development and outcome [ 227 , 228 , 229 , 230 ].…”
Section: Non-metabolic Risk Factors and Surrogatesmentioning
confidence: 99%